Hilding Rosenbergs beredskapsoratorium - Karlsson, Henrik (Svensk tidskrift för musikforskning / Swedish Journal of Music Research, 1993)
One Sunday evening in 1942 Hilding Rosenberg’s oratorio Svensk Lagsaga was given it’s first performance in Swedish radio. As opposed to Rosenberg’s other oratorios from the war years (Johannes uppenbarelse och Örtagårdsmästaren), Svensk Lagsaga is almost completely forgotten today. During the years 1940–1941 the military preparedness propaganda was at it’s strongest. The radio was the uniting link in the defense efforts. It is with this background Rosenbergs Svensk Lagsaga must be seen. Svensk Lagsaga was in great part composed for the radio. The oratorio had the motto ”Non vi sed concordia” – not through power, but through concord. The work thereby symbolizes two of the most repeated slogans of this time: concord and freedom under the law. On the surface the oratorio isn’t about the 1940’s. Rosenberg was inspired by medieval texts (county laws, stanzas from the Engelbrekt song) and two 1700th-century poems by Wivallius and Stiernhielm. The reviews of Svensk Lagsaga were comprehensive and written by the most influential critics of the day: Kurt Atterberg, Kajsa Rootzén, Curt Berg, William Seymer, Patrik Vretblad and Sten Broman. The critics characterized the oratorio in words typical of that time: “harsh”, “forceful nordic tone”, “pithy”, etc. Many of them found that the overall impression was incoherent, others noted Rosenberg’s masterly control of these means of expression. The oratorio holds a central position in Rosenberg’s production during the 1940’s, not the least from stylistic aspects and deserves well to be performed again in it’s entireity. Rosenberg himself meant that Svensk Lagsaga was the most ”nordic” work he had ever composed.